CLUSTERING AS A STRATEGY FOR NATURE-BASED TOURISM: A STUDY IN RAMMANG-RAMMANG, INDONESIA - Andi Bharry Batari Buana (Proceedings International Conference on Marine Tourism and Hospitality Studies, 2025)
This study aims to analyze the clustering system of the Rammang-Rammang tourism area and to evaluate the roles, collaboration, challenges, and opportunities among stakeholders in supporting sustainable destination management. The research employs a qualitative approach that combines interviews with tourists, local communities, and village managers with direct field observations of facilities and activities. The findings indicate that the clustering system in Rammang-Rammang has naturally developed into several zones, including riverboat tourism, karst caves, village-based tourism, and culinary areas, each of which is interrelated and contributes to the identity of the destination. Tourists perceive the natural attractions as highly unique, yet they also note limitations in facilities and infrastructure. The interviews further reveal that local communities play a central role as guides and service providers, while village authorities coordinate governance and the government provides infrastructure support. Collaboration among stakeholders has been positive but remains hindered by weak coordination, limited funding, and low environmental awareness among some visitors. Nevertheless, opportunities for development are significant, particularly in strengthening local economic activities, adopting digital-based promotion, and integrating conservation into tourism services. The study concludes that clustering not only strengthens destination identity but also promotes more effective stakeholder collaboration and supports sustainable tourism practices. Recommendations include improving communication among stakeholders, establishing sustainable financing mechanisms, and adopting a stronger conservation-based approach to tourism management.